Model of the influence of training, compensation, and work-life balance on employee performance with job satisfaction as an intervening variable - Manurung, Rianto; Afni, Riza; Tambunan, Susi Marta (Enrichment : Journal of Management, 2026)
This study aimed to analyze the influence of training, compensation, and work-life balance on employee performance with job satisfaction as an intervening variable. A quantitative explanatory design was used, and data were obtained from respondents through a structured Likert-scale questionnaire. Structural equation modeling was applied to examine the causal relationships among all variables. The findings showed that training, compensation, and work-life balance had a significant positive effect on job satisfaction. The results also revealed that job satisfaction had a significant positive effect on employee performance. Furthermore, job satisfaction partially mediated the influence of training and compensation on employee performance and fully mediated the effect of work-life balance on employee performance. These findings indicated that organizations that provided adequate training, fair compensation, and supportive work-life balance created higher levels of job satisfaction, which in turn enhanced employee performance. This study offered meaningful insights for organizations seeking to improve productivity through the development of effective human resource management practices